2016
DOI: 10.1136/bjsports-2015-095497
|View full text |Cite
|
Sign up to set email alerts
|

Effects and dose–response relationships of resistance training on physical performance in youth athletes: a systematic review and meta-analysis

Abstract: ObjectivesTo quantify age, sex, sport and training type-specific effects of resistance training on physical performance, and to characterise dose–response relationships of resistance training parameters that could maximise gains in physical performance in youth athletes.DesignSystematic review and meta-analysis of intervention studies.Data sourcesStudies were identified by systematic literature search in the databases PubMed and Web of Science (1985–2015). Weighted mean standardised mean differences (SMDwm) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
288
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(315 citation statements)
references
References 75 publications
18
288
1
8
Order By: Relevance
“…The NMT program used in this study incorporated a small plyometric component with a larger emphasis on resistance training, indicating that the improvements in change of direction speed may have been a combination of both the plyometric and resistance training. Change of direction speed is largely affected by sprinting speed, movement efficiency, and muscular strength (21). The NMT program in this study included resistance training exercises to improve lower-body strength and power with a focus on movement quality and technical efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The NMT program used in this study incorporated a small plyometric component with a larger emphasis on resistance training, indicating that the improvements in change of direction speed may have been a combination of both the plyometric and resistance training. Change of direction speed is largely affected by sprinting speed, movement efficiency, and muscular strength (21). The NMT program in this study included resistance training exercises to improve lower-body strength and power with a focus on movement quality and technical efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance training designed qualitatively and carried out under a professional is an effective strategy for improving physical and psychosocial characteristics of children as well as reducing sports-related injury rates (Faigenbaum and Myer, 2009). The regular resistance training increases muscle strength of children and adolescents (Faigenbaum et al, 1993), motor skills such as jumping (Lesinski et al, 2016) and increases bone development, facilitating weight control (Faigenbaum, 2007;Myer and Wall, 2006), improves body composition (Faigenbaum et al, 2009;Faigenbaum et al, 1993). Besides the known positive effects of resistance exercises on children's health and motor performance is to strengthen the distal and proximal parts of the long bones (such as ulna, femur and tibia ), humerus (Osbahr et al, 2002Reagan et al, 2002), articular cartilage and epiphysis.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the use of weighted ropes may also have additional advantages that are typically associated with plyometrics, such as improving upper-body strength and coordination for lower-body (7)(8)(17)(18). A recent systematic review and meta-analysis revealed that plyometric training programs have only small to medium-sized effects to improve measures of physical fitness and athletic performance, whereas complex training programs have predominantly larger effects (19). This might indicate that higher loads are needed during training to induce performance gains and could be considered to justify the comparison between weighted and standard jump rope training.…”
Section: Introductionmentioning
confidence: 99%